Discrimination between Sexes in "On the Basis of Sex" by Mimi Leder - Annisa Firdausy (LITERA KULTURA : Journal of Literary and Cultural Studies, 2022)
This paper discussed gender discrimination between men and women in Mimi Leder's "On the Basis of Sex (2018)" movie using the Marxist feminism perspective. Gender discrimination describes how women and men treated unequally in various aspects. “On the Basis of Sex” revealed how women demonstrate the equal treatment of men and women in all spheres. In the movie, a female lawyer got a case about denying tax deduction to a man petitioner. She understands that it can revolutionize her career. By using a theory of Marxist Feminism by Simone De Beauvoir, it helped to achieve this study’s aim. Beauvoir represented that women are independent through being feminists. This study used textual and film visual analysis in following discussions; women being degraded sexually and professionally, and factors that support woman to fight against gender discrimination. From the analysis, women are able to prove that through her struggle, she gets equal rights. Women's equality is the biggest problem in women's lives. Those continue to be limited by discrimination and social inequality.